Interactions Between Crabs and the Environment: Progress and Prospects From a Behavioral Perspective - Boshan Zhu; Dapeng Liu; Fang Wang (Reviews in Aquaculture, 2026)
As ecosystem engineers, crab behaviors not only reflect the physiological state and welfare of individuals but also act as regulators influencing the function and stability of aquaculture systems. However, research on the behavioral responses of cultured crabs to environmental factors remains incomplete, and studies on how their behaviors affect the environment are even more limited. To enhance productivity, welfare, and environmental sustainability and provide theoretical support for the optimization of crab culture systems, it is essential to clarify the interactions between the behavior of crabs and the environmental factors. This review synthesizes and summarizes the major environmental factors, physical (temperature, substrate and shelter, sound, hydrostatic pressure), chemical (dissolved oxygen, ammonia, pH, pollutants, salinity), and biological (prey, conspecifics, polyculture species, pathogens), and their impacts on various behavioral patterns of crabs, including feeding, foraging, grooming, mating, aggressive, territorial, burying, burrowing, sheltering behavior, and cannibalism. Decoding sensory processing and behavioral mechanisms in crabs is pivotal for breakthroughs in intelligent and welfare‐oriented crab culture. Additionally, we summarize the disturbances caused by crab behaviors—such as burrowing, feeding, and social interactions—on substrate water characteristics, microbial composition, and polyculture species. Based on these insights, we list future research and applications in crab behavior, including precise behavioral monitoring, group behavior evaluation, and aquaculture environmental management. We hope this review will encourage greater attention to the behavior of cultured animals, promoting the application of behavioral studies in crab culture and providing theoretical support for the industry's high‐quality development.

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.

Important but ignored: Research progress on crab foraging behaviour and its implications for aquaculture - Dapeng Liu; Boshan Zhu; Xiaoshou Liu; Fang Wang (Reviews in Aquaculture, 2024)
Crab fisheries play a crucial role in global fishery economics, but they heavily rely on wild catches. With the decline and exploratory limits of wild populations, expanding the scale and production of aquaculture becomes vital for the sustainability of crab fisheries. The development of crab aquaculture encounters significant dietary challenges, stemming from suboptimal formulated feeds and inefficient feeding management. Leveraging insights from crab foraging behaviours offers a promising solution to these issues; however, progress is hindered by a lack of comprehensive behavioural data and the underappreciation of these insights in aquaculture. To bridge this gap, we systematically examine the progress in studies of crab foraging behaviour, analysing the influences of predators, prey, and environmental characteristics, and discuss possibilities for future research and development in the field by combining these findings with the demands of aquaculture. This review identifies a discrepancy in research focus, with inadequate emphasis on the major cultured species and their behavioural responses to factors limiting aquaculture productivity, aiming to enhance our comprehension of crab foraging behaviour and facilitate growth in the crab industry.